Hepatocyte growth factor activator inhibitor-2 stabilizes Epcam and maintains epithelial organization in the mouse intestine - Kawaguchi, Makiko (Commun Biol, 2019)
Mutations in SPINT2 encoding the epithelial serine protease inhibitor hepatocyte growth factor activator inhibitor-2 (HAI-2) are associated with congenital tufting enteropathy. However, the functions of HAI-2 in vivo are poorly understood. Here we used tamoxifen-induced Cre-LoxP recombination in mice to ablate Spint2. Mice lacking Spint2 died within 6 days after initiating tamoxifen treatment and showed severe epithelial damage in the whole intestinal tracts, and, to a lesser extent, the extrahepatic bile duct. The intestinal epithelium showed enhanced exfoliation, villous atrophy, enterocyte tufts and elongated crypts. Organoid crypt culture indicated that Spint2 ablation induced Epcam cleavage with decreased claudin-7 levels and resulted in organoid rupture. These organoid changes could be rescued by addition of serine protease inhibitors aprotinin, camostat mesilate and matriptase-selective α-ketobenzothiazole as well as by co-deletion of Prss8, encoding the serine protease prostasin. These results indicate that HAI-2 is an essential cellular inhibitor for maintaining intestinal epithelium architecture.